Windows Server Hacks - Tulloch, Mitch (O'Reilly, 2011)
The tools, or hacks in this book reveal techniques that go well beyond basic management tasks found in most handbooks. Hacks range from those that deal with general administration to more esoteric hacks in the areas of network deployment, patch management, performance, security, and backup and recovery. No matter which Windows Server you use--NT, IIS, 2000, or 2003--Windows Server Hacks will put the knowledge and expertise of veteran system administrators to work for you.